INNOVATION IN FUNCTION OF CREATING IMAGE OF THE CITY AS A TOURIST DESTINATION - Đorđević, Saša M (International Journal of Economic Practice and Policy, 2013)
Cities, the most complex products on the market, cannot plead the market competitiveness unless clearly differentiated and with the created image. In support of the growing contemporary actualization of a city as a trademark or a brand, a wider range of possibilities for differentiation of an image comes into play, where innovation is considered as one of the more significant elements. Therefore, this paper discusses the creation of the image of a city, in context of innovation. Perception of the image of a city by tourists and tourist groups has innovation as a specific feature of city tourist identity. This is shown in this paper on the example of the French city of Angouleme, where city’s cultural capital contributed to transformation of identity and image, to revival of cultural life of the city, tourism development and launch of the entire region. This city has used a comics’ festival (Festival International de la Bande Dessinée Angouleme) to completely revitalize its medieval heritage, which was treated as a cult of the city and a source of pride of its inhabitants. Today, the mentioned festival in this city has become a "brand", and thanks to that city Angouleme – "Capital of comics”, the region – "a picturesque valley " and France – the most important country in Europe for comics publishing.
Keywords: innovation; creating the image of a city; transformation of the city's identity; market brand; brand concept